Pengembangan Permainan Question Wheel Sebagai Media Pengayaan pada Materi Keuangan Pemerintah Desa Kelas Xi di SMK Negeri 1 Sooko Mojokerto - Rachmawati, Yunia; Rochmawati, Rochmawati (Universitas Pendidikan Indonesia, 2021)
The purpose of this research is to produce media to enrich the Question Wheel game. The development model applied is the ADDIE model by Raiser and Mollenda. The development process is carried out according to the stages of the ADDIE model which consists of the analysis phase, design stage, development stage, implementation phase, and evaluation stage. This research is only limited to the development stage due to time constraints caused by the Covid-19 pandemic so that researchers cannot proceed to the next stage. After the development process is guided by the stages listed, then an assessment activity is carried out on the Question Wheel game enrichment media. In order to find out the feasibility of a developed media, research and validation activities were carried out by material experts, namely Accounting Teachers of SMK Negeri 1 Sooko Mojokerto and Lecturers in Accounting Education, State University of Surabaya, and media experts, namely Lecturers, Technology Education, State University of Surabaya. The results of the validity of the enrichment media development in the form of Question Wheel games from material experts with an average percentage of 89% in the